2013
DOI: 10.4102/pythagoras.v34i2.234
|View full text |Cite
|
Sign up to set email alerts
|

Proportional reasoning as a threshold to numeracy at university: A framework for analysis

Abstract: There is a generally acknowledged need for students to be quantitatively literate in an increasingly quantitative world. This includes the ability to reason critically about data in context. We have noted that students experience difficulty with the application of certain mathematical and statistical concepts, which in turn impedes progress in the development of students’ critical reasoning ability. One such concept, which has the characteristics of a threshold concept, is that of proportional reasoning. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…In their literature review, Tourniaire and Pulos (1985, p. 185) noted that this strategy of simply comparing the numerators (and ignoring the denominators) is 'a developmentally primitive strategy', but that 'it is still used with some frequency in adolescence'. We have also seen that this strategy is used by about half of the students in a university quantitative literacy course for law students (Lloyd & Frith, 2013). The results for Question 7 reveal that even in the top quarter, under two-thirds of the candidates could successfully compare fractions by reasoning alone (admittedly in a fairly complex, reading-intensive question).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…In their literature review, Tourniaire and Pulos (1985, p. 185) noted that this strategy of simply comparing the numerators (and ignoring the denominators) is 'a developmentally primitive strategy', but that 'it is still used with some frequency in adolescence'. We have also seen that this strategy is used by about half of the students in a university quantitative literacy course for law students (Lloyd & Frith, 2013). The results for Question 7 reveal that even in the top quarter, under two-thirds of the candidates could successfully compare fractions by reasoning alone (admittedly in a fairly complex, reading-intensive question).…”
mentioning
confidence: 81%
“…From our experience of teaching quantitative literacy to university students, we have observed that proportional reasoning is a troublesome concept; it is difficult to learn and takes a long time to learn. Consequently, we regard proportional reasoning as a 'threshold concept' (Meyer & Land, 2003) for all academic quantitative literacy (Frith & Lloyd, 2014;Lloyd & Frith, 2013). This threshold concept, once mastered, opens a gateway to thinking differently about quantities.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold is reached when proportional reasoning is used automatically and the logical process of this reasoning can be expressed coherently and concisely, making use of appropriate language. We were thus able to conclude that most of our students, in reasoning with absolute numbers rather than relative numbers, had not reached the threshold of reasoning qualitatively about quantities involving fractions -in fact, many were still at the pre-liminal stage of understanding proportional comparison (Lloyd and Frith 2013).…”
Section: Preceding Workmentioning
confidence: 99%
“…The proportion of students who were reasoning with absolute quantities was disappointingly high. For a detailed description of this initial process, see Lloyd and Frith (2013).…”
Section: Preceding Workmentioning
confidence: 99%
See 1 more Smart Citation